The role of field training in improving cognitive development and building personality among psychological counseling students at Al Alsharqiyah University in the Sultanate of Oman - Al-Obaidani, Khulood Ahmed Amur (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the role of field training on psychological counseling students, and to measure the role from the cognitive side and build personality. The study followed the analytical descriptive approach, and adopted the questionnaire as a tool for the study. It was applied to a sample of (60) female students majoring in psychological counseling during the fall 2022 semester. The results of the study revealed that the field training contributed to improving the cognitive side of the students with a high impact force, as the general arithmetic mean was (4.16). The results also showed the effect of field training on personality building with a moderate degree of impact, as the general arithmetic mean was (3.87). One of the most prominent results on the open-ended questions in terms of benefit. Anger and making appropriate decisions, as well as how to deal with different types of personalities in the work environment, and converting what has been studied in theory into an applied aspect. In the light of the results of the study, the current study recommended the need to continue applying field training to university students in various disciplines, and to provide students with the knowledge and training skills necessary to strengthen the practical side.
Keywords: Cognitive development; personality building; psychological counseling students